The Impact of Consumption of Protein and Carbohydrate Sources on Stunting in Toddlers 24-59 months at Gleno Inpatient Health Center, Ermera Municipality, Timor-Leste - Jerminal Magno; Marcos Carvalho; Rodinho da Conceição; Angela Soares; Aniceto da Conceição Pacheco; Levi Anatolia Soares Maia Exposto (Public Health and Safety International Journal, 2026)
Stunting is a serious condition that affects children and significantly hinders their growth and development. Globally, at least 162 million children under the age of five are affected by stunting. A study conducted between 2020 and 2024 involved 177 children aged 24 to 59 months, including 85 boys and 92 girls. The study aimed to investigate the impact of protein and carbohydrate intake on stunting in toddlers within this age range. This research utilized a quantitative design with a cross-sectional approach. The target population consisted of mothers who brought their children to the Gleno Inpatient Community Health Center, resulting in 177 respondents. Data analysis was performed using the chi-square test, with support from SPSS software (Version 21.0). The results of the chi-square test indicated a significant relationship between protein intake and the incidence of stunting, with a p-value of 0.05, which is greater than 0.01. Similarly, the analysis of carbohydrate intake also yielded a p-value of 0.05, suggesting a significant relationship between carbohydrate consumption and the incidence of stunting. In conclusion, the findings suggest that protein and carbohydrate consumption negatively impact stunted children aged 24 to 59 months at the Gleno Inpatient Health Center in 2024, with an effect size of 6.3%. This implies that while nutritional intake appears to be satisfactory, the implementation of interventions to address stunting is not optimal.